Use of electrophoretic methods for the rapid analysis of proteins of Antarctic region marine organisms - Raksha, N. G.; Gladun, D. V.; Savchuk, O. M.; Ostapchenko, L. I. (Ukrainian Antarctic Journal, 2014)
Several methodological approaches for integrated rapid analysis of tissue samples of marine organisms on an example of Odontaster validus and Euphausia superba were tested. These methods can be recommended for analysis of the protein composition and enzymatic activity of tissue samples from other organisms of Antarctic region that represents a specific biotechnological interest.